Application of prohexadione calcium in strawberry seedlings cv. Pircinque Aplicación de prohexadiona de calcio en plántulas de fresa cv. Pircinque - Molano Z.P.* (2021)
© 2021, Universidad Pedagogica y Tecnologica de Colombia. All rights reserved.In Brazil, strawberry production depends on the importation of seedlings from different countries, with variable levels of adaptation, different cold requirements, and high costs. The national production of seedlings with good genetic, physiological and phytosanitary quality is a viable alternative for Brazilian strawberry producers. The objective was to evaluate the effect of applications with different concentrations and timing using calcium prohexadione (ProCa) (growth retardant in various cultivated species) on magnitude changes in propagation structures, growth and development of strawberry seedlings cv. Pircinque, productive behavior, and fruit quality. This experiment was carried out in the Agricultural Sciences Center of the Santa Catarina State University (CAV-UDESC) in Lages/SC (Brazil), with a 5 x 2 factorial design, five concentrations of prohexadione calcium (0, 100, 200, 300 and 400 mg L-1), and two application schedules (20 and 30 days after planting the rooting stolon). In the seedlings, the following were evaluated: number of leaves, crown diameter, seedling height, and leaf area. The parameters evaluated in the strawberry plants were: number of fruits per plant, average fruit weight, total fruit weight, and dry weight of leaves and crowns during the 2019/2020 cycle. Additionally, firmness, total soluble solids (TSS), titratable acidity (TA), and ratio were evaluated. Applying ProCa significantly reduced vegetative growth and increased physiological responses in the ‘Pircinque’ strawberry seedlings, such as leaf area and height for both application periods. On the other hand, the ProCa concentrations did not influence the number of fruits, fruit mass per plant, or fruit quality parameters, with the exception of firmness, which was favored by the 400 mg L-1 concentration. The results were related to the application timing, where, at 20 DAT, the highest values of the morphological variables in the seedlings and plants were observed. On the contrary, applications at 30 DAT decreased the number of commercial fruits per plant.